An Adolescent Female with Bipolar Disorder Presenting with Lithium-Induced Hyperthyroidism - Pratibha Rana; Patria Alba Aponte; Ghufran Babar (Case Reports in Endocrinology)
Lithium therapy has been associated with several endocrine disorders including thyroid dysfunction, diabetes insipidus, and hyperparathyroidism. While its suppressive effect on thyroid function is well known, it is very rare to observe lithium-induced hyperthyroidism especially in the pediatric population. Here, we describe a case of lithium-induced hyperthyroidism in an adolescent female with bipolar disorder. The patient is a 17-year-old female who was treated with lithium for bipolar disorder and presented with symptoms and laboratory findings consistent with hyperthyroidism. Since thyroid autoantibodies were negative, thyroid dysfunction was attributed to lithium toxicity. Indeed, her clinical and biochemical hyperthyroid state resolved after stopping lithium therapy. Lithium-associated hyperthyroidism can occur in the pediatric population. We propose close monitoring of thyroid hormone levels in children on lithium therapy.